KEPUTUSAN INVESTASI PADA PENGANGGARAN MODAL DALAM PERSPEKTIF CONSERVATISM - Arofatul Hidayah; Hilwatut Tilawah (PT Naureen Digital Education, 2026)
A company certainly has plans for the capital it possesses, and this is a necessity as it will lead to matters that can influence the company, one of which is investment decisions. Proper capital budgeting will support the right decisions. The results of these investment decisions will affect the company's performance. However, in essence, due to the presence of bias or misalignment of available information, it can affect the effectiveness of the decisions made. One such bias that can influence investment decisions is the conservatism bias, which is an effect caused by the managerial intention to disregard or be slow to react to the latest information due to a comfortable condition based on previous experiences. Using a literature study approach, by studying books, references, and previous research findings, the result shows that conservatism bias has a positive relationship with investor behavior and financial risk tolerance. To improve the effects of this bias, substantial improvements need to be made in the type, form, and method of communication of information in financial decision-making.